The Role of sustainable finance in driving environmental, social and governance (ESG) based investments - Irianto, Ellen D. Oktanti; Kesuma, Muhammad Ramadhani; Aini, Rohana Nur; Henrika, Margareth; Ariswati, Lusiana Desy (JEMBA: Jurnal Ekonomi Pembangunan, Manajemen & Bisnis, Akuntansi, 2025)
This research discusses the application of Environmental, Social, and Governance (ESG) principles in investment decision-making and their impact on long-term financial performance and investment risk management. The research aims to provide a clearer understanding of how ESG principles are applied in investment decisions, as well as assess their impact on long-term stability. The method used is a qualitative literature review approach, analyzing various related studies. The results indicate that integrating ESG principles into investments can enhance financial performance, reduce risks associated with environmental and social issues, and support the achievement of sustainable development goals. Despite challenges in ESG implementation, such as inconsistencies in reporting and lack of transparent data, there are significant opportunities for companies and investors to leverage ESG as a sustainable and profitable investment strategy. This study provides recommendations for companies, regulators, and investors on how best to integrate ESG into their investment strategies